Diagnosis applied to Public Relations: an analysis of the theoretical and empiric aspects - Baseggio, Ana Luisa (Organicom, 2009)
Public Relations, which is an activity that concerns communication and relationship, relates to the construction and consolidation of a favorable perception of organizations by their publics of interest. This article presents a study of the conduction of Public Relations diagnoses. It has been developed based on theoretical and empiric surveys, analyzing the opinion of the scientific community and of professionals who are active in the area, with a critical assessment of the considerations and reflections concerning the exercise of communication and the favorable or risky conditions that could arise.